Perfection in Matthew 5:48a as ‘wholehearted obedience’: An intertextual study - Coetsee, Albert J. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
This article investigated the apparent unattainable ideal of Matthew 5:48 that the addressees should ‘be perfect … as your heavenly Father is perfect’. The main hypothesis of the article is that a better understanding of the most likely Old Testament backgrounds to Matthew 5:48, namely Leviticus 19:2 and Deuteronomy 18:13, leads to a more nuanced interpretation of the two occurrences of ‘perfect’ in the verse, and the realisation that the two usages of ‘perfect’ in Matthew 5:48 are similar but not identical. The article employed an intertextual study, beginning with an investigation of the text and context of Matthew 5:48 for a provisional interpretation of the verse. This was followed by an investigation of Luke 6:36 and its comparison to Matthew 5:48 to determine the unique emphases of the latter. The article then investigated the original context and meaning of both Leviticus 19:2 and Deuteronomy 18:13, considering their potential relevance to interpreting Matthew 5:48. Penultimately, the provisional conclusions of the investigation of Leviticus 19:2 and Deuteronomy 18:13 were tested by investigating the use of perfection language elsewhere in Matthew. The article concluded by drawing the lines together and reflecting on the meaning of Matthew 5:48 within its broader context. The findings suggest that Leviticus 19:2 and Deuteronomy 18:13 influence the interpretation of Matthew 5:48. Both passages emphasise wholehearted obedience to God, indicating that ‘perfect’ in Matthew 5:48a should be interpreted as ‘wholehearted obedience’ to God, rather than moral perfection per se. Furthermore, the twofold use of ‘holy’ in Leviticus 19:2 implies that ‘perfect’ in Matthew 5:48b should be interpreted as moral perfection. Contribution: This article contributed to the meaning and interpretation of Matthew 5:48 by indicating how the most likely Old Testament backgrounds of the verse, namely Leviticus 19:2 and Deuteronomy 18:3, influence its interpretation.